Safety and efficacy of baricitinib in steroid‐resistant or relapsed immune thrombocytopenia: An open‐label pilot study - Zhao, Peng; An, Zhuo‐Yu; Fu, Hai‐Xia; Liu, Hui‐Xin; Feng, Cheng‐Jie; Huang, Qiu‐Sha; Wu, Jin; Wu, Ye‐Jun; Yang, Li‐Ping; Qu, Qing‐Yuan; Chen, Yu‐Xiu; Li, Meng‐Lin; et al. (American journal of hematology, 2024)
Patients with steroid‐resistant or relapsed immune thrombocytopenia (ITP) suffer increased bleeding risk and impaired quality of life. Baricitinib, an oral Janus‐associated kinases (JAK) inhibitor, could alleviate both innate and adaptive immune disorders without inducing thrombocytopenia in several autoimmune diseases. Accordingly, an open‐label, single‐arm, phase 2 trial (NCT05446831) was initiated to explore the safety and efficacy of baricitinib in ITP. Eligible patients were adults with primary ITP who were refractory to corticosteroids and at least one subsequent treatment, and had platelet counts below 30 × 109/L at enrolment. Participants received baricitinib 4 mg daily for 6 months. The primary endpoint was durable response at the 6‐month follow‐up. A total of 35 patients were enrolled. Durable response was achieved in 20 patients (57.1%, 95% confidence interval, 39.9 to 74.4), and initial response in 23 (65.7%) patients. For patients responding to baricitinib, the median time to response was 12 (IQR 6–20) days, and the median peak platelet count was 94 (IQR 72–128) × 109/L. Among the 27 patients undergoing extend observation, 12 (44.4%) remained responsive for a median duration of approximately 20 weeks after baricitinib discontinuation. Adverse events were reported in 11 (31.4%) patients, including infections in 6 (17.1%) patients during the treatment period. Treatment discontinuation due to an adverse event was reported in 2 (5.7%) patients. Evidence from this pilot study suggested that baricitinib might be a novel candidate for the armamentarium of ITP‐modifying agents. Future studies are warranted to validate the safety, efficacy, and optimal dosing of baricitinib in patients with ITP.